2021
DOI: 10.3390/healthcare9060689
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Contextual Factors Effects and Their Implications for Italian Physiotherapists: Findings from a National Cross-Sectional Study

Abstract: An online cross-sectional survey was conducted using Google Docs software. The aim was to understand the management of contextual factors and to identify which are most relevant and which clinicians underestimate. A total of 1250 physiotherapists were chosen from the database of the Manual Therapists group mailing list (GTM-IFOMPT MO) from July to August 2020. A total of 699 responses were received that were considered valid (56%). Participants (40.83%) identified contextual factors (CFs) as “any element, even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 44 publications
2
19
1
3
Order By: Relevance
“…However, such practice is not routinely implemented in clinical practice ( Rossettini et al, 2019 , 2020c ). As emerged in previous surveys, clinicians involved in MSK care report difficulties in managing patients’ expectations and avoid nocebo-related effects ( Palese et al, 2019a ; Cadorin et al, 2020 ; Rossettini et al, 2020b ; Bisconti et al, 2021 ). This lack highlights the need for clinicians to have a framework that they can apply in everyday practice.…”
Section: Introductionmentioning
confidence: 93%
“…However, such practice is not routinely implemented in clinical practice ( Rossettini et al, 2019 , 2020c ). As emerged in previous surveys, clinicians involved in MSK care report difficulties in managing patients’ expectations and avoid nocebo-related effects ( Palese et al, 2019a ; Cadorin et al, 2020 ; Rossettini et al, 2020b ; Bisconti et al, 2021 ). This lack highlights the need for clinicians to have a framework that they can apply in everyday practice.…”
Section: Introductionmentioning
confidence: 93%
“…Contextual factors (CF) are various elements deriving from a patients' interactions with practitioners and the therapeutic arena that influence disease processes and therapeutic outcomes ( 2 , 3 ). Whilst positive CF may induce placebo effects, negative CF may induce nocebo effects resulting in adverse effects ( 4 , 5 ).…”
Section: Considerations For Designing Rigorous Research On Placebo An...mentioning
confidence: 99%
“…Whilst positive CF may induce placebo effects, negative CF may induce nocebo effects resulting in adverse effects ( 4 , 5 ). However, studies assessing specific CF have yielded mixed results on their contribution to placebo/nocebo effects ( 2 , 6 , 7 ). This heterogeneity in outcomes have prompted investigating the context of how the CFs are assessed.…”
Section: Considerations For Designing Rigorous Research On Placebo An...mentioning
confidence: 99%
“…Bisconti and col. conducted a study with physical therapists in 2021 10 to understand the management of contextual factors and identify the most relevant ones and the underestimated ones by professionals. The contextual factors included physical therapists' characteristics, patients' characteristics, patient/ physical therapist relationship, treatment, and therapeutic setting.…”
Section: Figure 2 Articles Per Year Of Publicationmentioning
confidence: 99%
“…The results highlighted that participants considered any voluntary or involuntary element with which they interacted during the treatment as contextual factors, which made up the therapeutic setting. It then found that physical therapists considered communication strategies -e.g., stimulating positive expectations in patients toward successful therapies, having a therapeutic relationship with patients, and using active clinical listening in the treatment -highly important to achieve better therapeutic results 10 .…”
Section: Figure 2 Articles Per Year Of Publicationmentioning
confidence: 99%